2012
DOI: 10.4161/derm.22519
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic aging

Abstract: Age-associated skin lesions linked to UV radiation (UVR) include actinic keratosis, non-melanoma skin cancer—such as basal cell carcinoma and squamous cell carcinoma—lentigo senilis and lentigo maligna. Their incidence is increasing worldwide, mainly due to exaggerated UV exposure and to an aging population. Early diagnosis and therapy of pre-malignant cutaneous lesions is crucial for the secondary prophylaxis of invasive and highly aggressive skin cancers. Combined efforts to increase public awareness, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…UVB exposure causes photoaging, wrinkling, and pigmentation [ 22 ]. The UVB-irradiated group treated with AFWE showed no alteration in cellular morphology ( Figure S2C ), and no cell death was seen in the control or positive control groups ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UVB exposure causes photoaging, wrinkling, and pigmentation [ 22 ]. The UVB-irradiated group treated with AFWE showed no alteration in cellular morphology ( Figure S2C ), and no cell death was seen in the control or positive control groups ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is obvious that the activation of PKC, P38, and deactivation of ERK are all known to regulate the IVL expression. UVB exposure causes photoaging, wrinkling, and pigmentation [22]. The UVB-irradiated group treated with AFWE showed no alteration in cellular morphology…”
Section: Afwe and Io Both Confirm The Regulatory Role Of Pkc And Mapk Signaling In Ivl Expressionmentioning
confidence: 91%
“…It was shown that damage to ESC DNA by low-dose ionizing radiation significantly induced DSBs-mediated chromatin modifications and that DSBs may also be passed on to their differentiated cell lineages [ 44 ]. Persistent exposure to UVR also increased DNA damaged lesions and mutations and led to premature aging or carcinogenesis of the skin [ 45 ].…”
Section: Uv-induced Depletion Of Skin Stem Cells: a Multipronged Amentioning
confidence: 99%
“…Intrinsic aging is a normal physiological process characterized by decreased cell proliferation in basal layers and accumulation of senescent cells in epidermis and dermis resulting in skin dryness, thinning, fine wrinkles, itching [ 1 ], and susceptibility to many skin disorders, such as infections, autoimmune disorders, and malignancy [ 2 ]. External factors, including pollutants, smoking, diet, temperature, and especially ultraviolet and infrared radiation have larger influence on aggravation of inflammation and aging phenotypes such as wrinkles, irregular pigmentation, skin dryness, and decreased dermal and epidermal thickness [ 3 ].…”
Section: Introductionmentioning
confidence: 99%